Physicochemical and toxicological profiling of ash from the 2010 and 2011 eruptions of Eyjafjallajökull and Grímsvötn volcanoes, Iceland using a rapid respiratory hazard assessment protocol. - Horwell, C J; Baxter, P J; Hillman, S E; Calkins, J A; Damby, D E; Delmelle, P; Donaldson, K; Dunster, C; Fubini, B; Kelly, F J; Le Blond, J S; Livi, K J T; et al. (Environmental Research, 2013)
The six week eruption of Eyjafjallajökull volcano in 2010 produced heavy ash fall in a sparsely populated area of southern and south eastern Iceland and disrupted European commercial flights for at least 6 days. We adopted a protocol for the rapid analysis of volcanic ash particles, for the purpose of informing respiratory health risk assessments. Ash collected from deposits underwent a multi-laboratory physicochemical and toxicological investigation of their mineralogical parameters associated with bio-reactivity, and selected in vitro toxicology assays related to pulmonary inflammatory responses. Ash from the eruption of Grímsvötn, Iceland, in 2011 was also studied. The results were benchmarked against ash from Soufrière Hills volcano, Montserrat, which has been extensively studied since the onset of eruptive activity in 1995. For Eyjafjallajökull, the grain size distributions were variable: 2-13 vol% of the bulk samples were <4 µm, with the most explosive phases of the eruption generating abundant respirable particulate matter. In contrast, the Grímsvötn ash was almost uniformly coarse (<3.5 vol%<4 µm material). Surface area ranged from 0.3 to 7.7 m2 g(-1) for Eyjafjallajökull but was very low for Grímsvötn (<0.6 m2 g(-1)). There were few fibre-like particles (which were unrelated to asbestos) and the crystalline silica content was negligible in both eruptions, whereas Soufrière Hills ash was cristobalite-rich with a known potential to cause silicosis. All samples displayed a low ability to deplete lung antioxidant defences, showed little haemolysis and low acute cytotoxicity in human alveolar type-1 like epithelial cells (TT1). However, cell-free tests showed substantial hydroxyl radical generation in the presence of hydrogen peroxide for Grímsvötn samples, as expected for basaltic, Fe-rich ash. Cellular mediators MCP-1, IL-6, and IL-8 showed chronic pro-inflammatory responses in Eyjafjallajökull, Grímsvötn and Soufrière Hills samples, despite substantial differences in the sample mineralogy and eruptive styles. The value of the pro-inflammatory profiles in differentiating the potential respiratory health hazard of volcanic ashes remains uncertain in a protocol designed to inform public health risk assessment, and further research on their role in volcanic crises is warranted.